Gerakan Back Exercise untuk Mengurangi Keluhan Nyeri Punggung Bawah Pekerja Penambang Pasir di Depo Desa Jumoyo, Salam, Magelang - Harnum Septiani; Lilik Hendarini; Sri Muryani (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Sand miners at the Depo in Jumoyo Village in Magelang have not received occupational health attention, particularly with work-related risks that may result in low back pain. One method to reduce low back pain is back exercise movement that was designed to strengthen some mus- cles. The purpose of this study was to identify pain reduction differences between before an after the exercise is applied by doing a quasi experiment with non-equivalent control group design. As the study sample was 30 sand miners in Jumoyo Depo who were non-randomly selected by using accidental sampling technique. Study results show that there was an increase in the num- ber of miners who complaining lower back pain in the category of “less pain” and “pain does not exist”. Data analysis with Wilcoxon test at 0,05 significance level show that there was a signifi- cant complaint reduction between before and after back exercise activity, in the experimental group (p value 0,001), meanwhile in control group the reduction was not observed.